Análisis de gestión del talento humano en el Seguro Social Campesino basado en la satisfacción al usuario de la Parroquia Canuto. - Cusme Párraga, Verónica Johanna (2015)
Public institutions like government agencies are obligated to provide quality services to the public. The main objective of this work is to examine the management of human talent in the Rural Health Insurance building of Canuto parish to improve user satisfaction. For the purpose of collecting relevant information investigative techniques were used such as: observation, interview and survey, which allowed to identify the shortcomings of the human talent management; as well as, the causes that generate discomfort to the users. Once identified the flaws within dependencies the manuals functions make it difficult for the servers to knowledge all the functions involve and therefore do perform satisfactory service, the limited budget makes almost impossible the recruitment of more staff, they do not have enough material and technological resources for the development of its functions in addition is not measured the satisfaction or opinion of the service by the user, despite the fact that it is regulated in the Constitution of the Republic of Ecuador. From this study was verify the need of public institutions carry out in improvement plans arising objectives, strategies and actions that allow to meet the needs of the users and at the same time feel satisfied by the service.